- #36
benorin
Homework Helper
- 1,443
- 191
To start with separate the integrals like this
$$I=\int_0^\infty\int_0^\infty e^{-\tfrac{\lambda ^3}{xy}}x^{-\tfrac{2}{3}}y^{-\tfrac{1}{3}}\, dx\, dy \cdot \underbrace{\left( \int_0^\infty e^{-x}\, dx\right) ^2}_{=4 \Gamma ^2 (2)=4}$$
both converge as they should. Then to work on the left hand integrals by transformations. Will edit with the rest later.
$$I=\int_0^\infty\int_0^\infty e^{-\tfrac{\lambda ^3}{xy}}x^{-\tfrac{2}{3}}y^{-\tfrac{1}{3}}\, dx\, dy \cdot \underbrace{\left( \int_0^\infty e^{-x}\, dx\right) ^2}_{=4 \Gamma ^2 (2)=4}$$
both converge as they should. Then to work on the left hand integrals by transformations. Will edit with the rest later.